2021
DOI: 10.1186/s13065-020-00727-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polysaccharides from different species of brown seaweed using saccharide mapping and chromatographic analysis

Abstract: Brown seaweed polysaccharides (BSPs) are one of the primary active components from brown seaweed that has a range of pharmaceutical and biomedical applications. However, the quality control of BSPs is a challenge due to their complicated structure and macromolecule. In this study, saccharide mapping based on high-performance liquid chromatography (HPLC), multi-angle laser light scattering, viscometer, and refractive index detector (HPSEC-MALLS-Vis-RID), and Fourier transform infrared (FT-IR) were used to discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 47 publications
2
12
1
Order By: Relevance
“…Thus, our laboratory has worked on the synthesis of 4,4′-(arylmethylene)bis(1-phenyl-3-methyl-1 H -pyrazole-5-ols) and assayed them against in vitro models previously implemented in our laboratory. We found that these compounds have good antioxidant activity in vitro, as well as cytotoxicity against the RKO cell line [ 12 ]. We found good leishmanicidal activity against promastigotes of Leishmania mexicana and the evaluation of the anti-trypanosomatid activity of these compounds is in progress and will be reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our laboratory has worked on the synthesis of 4,4′-(arylmethylene)bis(1-phenyl-3-methyl-1 H -pyrazole-5-ols) and assayed them against in vitro models previously implemented in our laboratory. We found that these compounds have good antioxidant activity in vitro, as well as cytotoxicity against the RKO cell line [ 12 ]. We found good leishmanicidal activity against promastigotes of Leishmania mexicana and the evaluation of the anti-trypanosomatid activity of these compounds is in progress and will be reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of heteroaromatic compounds containing pyridine or imidazole core are associated with diverse pharmacological properties such as antimicrobial, anticonvulsant, antiviral, antifungal, etc. [ 25 , 26 , 27 , 28 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the reports, functional groups containing oxygen and sulfur donors have a potential role in fighting cancer cells and bacteria [ 22 , 23 ]. Additionally, imidazole and pyridine are well-known pharmacists whose derivatives are currently used against various diseases [ 24 , 25 , 26 , 27 , 28 ]. In our research, we employed the N,O-donor ligands, in which imidazole and pyridine were substituted by -OH, -CHO, and -COOH functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Azole compounds of the type 1,2,3-triazoles attract more attention as they have excellent biological and physical properties [ 116 , 117 ]. These heterocycles can be obtained by the copper (I) catalyzed 1,3-dipolar cycloaddition reaction of azide and alkyne, as shown in previous reports.…”
Section: Synthetic Methods For Highly Active Compounds Against Fox Speciesmentioning
confidence: 99%